The Influence of consumption values on housing furniture satisfaction among working women in Jeddah, Saudi Arabia - Makkawi's, Fattwo Abdul Rahman; Hashim, Ahmad Hariza; Jasmine, Leby Lau (Human Resource Management Academic Research Society, 2021)
The types and proper arrangement of furniture can assist those who did households chores to perform efficiently and effectively. Thus, it is important especially for working women to be satisfied with their furniture as they come back from work and continue doing home activities. This paper presents the values that influence working women in Jeddah region, Saudi Arabia in their home. Quantitative approach using model of consumption values was adopted for this study. A sample of 350 Saudi working women selected from those working for the government sectors in Jeddah. Questionnaire was sent to these respondents through their respective e-mails. Data collected were later test for normality and reliability and multiple regression analysis was conducted in SPSS to test on the predictors of the consumption values on furniture satisfaction. The results show that, functional, emotional, and conditional values had a significant positive relationship, while social and epistemic values did not show significant relationship with home furniture. Hence, by gaining better insights and understanding of consumption values, it will be able to exhibit and enhance more working women lifestyle in Jeddah, Saudi Arabia and help them achieve work life balance between work and home through the use of home furniture.